Evaluation of the Foreign Exchange Management Act - Upasana (Innovative Research Thoughts, 2017)
A unique opportunity for academics to examine the faults of the federal government has arisen on the 200th anniversary of the 1819 Supreme Court decision McCulloch v. Maryland. FEMA's shortcomings in “Puerto Rico during and after Hurricane Maria brought attention to flaws in the Robert T. Stafford Disaster Relief and Emergency Assistance Act. For a legislation to be upheld as constitutional under McCulloch's interpretation of Article I, Section 8, the law must be necessary and appropriate for the government to carry out its enumerated functions. Even a well-drafted law passed by Congress for the betterment of the general welfare may be necessary, but not rise to the level of proper, as demonstrated by the stark contrast between the massive funding allocated for disaster relief under the Stafford Act and FEMA's catastrophic failure to provide meaningful aid to vulnerable populations in Puerto Rico in the Fall of 2017. McCulloch's insistence that laws adhere to the letter and spirit of the Constitution and anti-subordination interpretations of the Fifth and Fourteenth Amendments, which call for equal protection to be pursued in light of the lived experience of vulnerable and minority populations, meaningfully inform the standard of propriety at play here.